Pengaruh Penggunaan Metode Mengajar Bervariasi Terhadap Prestasi Belajar Siswa Dalam Mata Pelajaran PAI Di SMK Ciledug Al-Musaddadiyah Garut - Raito, Raito; Sarita, Dede (STAI Al-Musaddadiyah Garut, 2022)
Academic achievement remains a significant issue due to several factors: lack of student engagement with the material presented, indifference among students, and passive attitudes in the classroom. Therefore, utilizing a variety of teaching methods is a viable solution to address these student-related problems. This study aims to describe the influence of using diverse teaching methods in Islamic Religious Education (IRE) on students' academic performance. The research adopts a descriptive quantitative approach. Data collection methods include observation, document studies, and questionnaires distributed to 20 students who served as the sample for this study. Data analysis was conducted using statistical methods. The findings indicate that the average effectiveness of varied teaching methods is 4.00, which falls within the interval of 4.01-5.00, categorized as